The Spanish Cinema of Journalists from Dictatorship to Democracy: A Comparative Analysis between Franco’s Cinema and the Cinema of Transition (1942-1983 - Serrano Martín, Carlos; Angulo Egea, Maria (Cuadernos de Documentación Multimedia, 2025)
This paper analyses and compares the cinematographic profile of the Spanish journalist during the dictatorship of Francisco Franco and during the Transition. A content analysis has been carried out on 19 films shot and released between 1942 and 1983. The TRANSLITEME portal, a project open to the continuous incorporation of new works that may be relevant for the cultural study of the Transition, generated by the ‘Transficción’ group of the Government of Aragón, has played an important role in this research.